Metabolomic approach for rapid identification of antioxidants in clinacanthus nutans leaves with liver protective potential - Ng, Kai Song; Tan, Sheri-Ann; Bok, Chui Yin; Loh, Khye Er; Ismail, Intan Safinar; Yue, Chen Son; Loke, Chui Fung (MDPI AG, 2022)
Antioxidants are currently utilized to prevent the occurrence of liver cancer in non-alcoholic fatty liver disease (NAFLD) patients. Clinacanthus nutans possesses anti-oxidative and anti-inflammatory properties that could be an ideal therapy for liver problems. The objective of this study is to determine the potential antioxidative compounds from the C. nutans leaves (CNL) and stems (CNS). Chemical- and cell-based antioxidative assays were utilized to evaluate the bioactivities of CNS and CNL. The NMR metabolomics approach assisted in the identification of contributing phytocompounds. Based on DPPH and ABTS radical scavenging activities, CNL demonstrated stronger radical scavenging potential as compared to CNS. The leaf extract also recorded slightly higher reducing power properties. A HepG2 cell model system was used to investigate the ROS reduction potential of these extracts. It was shown that cells treated with CNL and CNS reduced innate ROS levels as compared to untreated controls. Interestingly, cells pre-treated with both extracts were also able to decrease ROS levels in cells induced with oxidative stress. CNL was again the better antioxidant. According to multivariate data analysis of the 1H NMR results, the main metabolites postulated to contribute to the antioxidant and hepatoprotective abilities of leaves were clinacoside B, clinacoside C and isoschaftoside, which warrants further investigation.